Can Alveolar-Arterial Oxygen Pressure Difference be used to Diagnose Acute Respiratory Distress Syndrome in Pneumonia Patients? - Wang, Ling; Wang, Wanling (Journal of Current Scientific Research, 2022)
Alveolar-arterial oxygen pressure difference (P(Aa)O2) can reflect pulmonary ability to exchange oxygen; it shows good correlation with the oxygenation index (OI), which is important in diagnosing acute respiratory distress syndrome (ARDS). This study explored the ability of P(Aa)O2 in diagnosing ARDS in pneumonia patients. Methods We selected patients with community-acquired pneumonia and sepsis in the intensive care unit (ICU) of the People’s Hospital of Qiandongnan Miao and Dong Autonomous Prefecture; we measured P(Aa)O2 and the OI under anoxic conditions upon their admittance to the ICU. We divided the patients into ARDS and non-ARDS groups. We compared the differences in P(Aa)O2 and OI; we analyzed the correlation between P(Aa)O2 and ARDS. To assess the diagnostic ability of P(Aa)O2 for ARDS, we drew the receiver operating characteristic (ROC) curve. Result We found that P(Aa)O2 in the ARDS group was greater than in the non-ARDS group (t = 8.875, P <0.001); the OI in the ARDS group was smaller than in the non-ARDS group (t = –6.956, P <0.001). There was a positive correlation between P(Aa)O2 and ARDS (r = 0.718, P <0.001). The area under the ROC curve for P(Aa)O2 in the diagnosis of ARDS was 0.931 (0.873–0.988); the cutoff value was 214.70 mmHg, the sensitivity was 89.50%, and the specificity was 85.00%. Conclusion We conclude that P(Aa)O2 is a good reference index in diagnosing ARDS.
Keywords: alveolar-arterial oxygen pressure difference; community-acquired pneumonia; diagnosis; sepsis; acute respiratory distress syndrome; oxygenation index